Prediction of Substance Use Tendency Based on Cognitive Avoidance and Distress Tolerance in University Students - Javidi , Sanaz; Karami, Abolfazl (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to predict substance use tendency among university students based on levels of cognitive avoidance and distress tolerance.Methods and Materials: A descriptive-correlational design was employed with a sample of 370 students from the Islamic Azad University, West Tehran Branch, selected through convenience sampling. Participants completed three standardized instruments: the Substance Use Tendency Questionnaire (Weed & Butcher, 1992), the Distress Tolerance Scale (Simons & Gaher, 2005), and the Cognitive Avoidance Questionnaire (Sexton & Dugas, 2008). Descriptive statistics, Pearson correlation, and multiple regression analyses were conducted using SPSS software.Findings: The results showed that distress tolerance was negatively correlated with substance use tendency, while cognitive avoidance was positively correlated. Multiple regression analysis revealed that both distress tolerance (β = -0.364, p < 0.001) and cognitive avoidance (β = 0.285, p < 0.001) significantly predicted substance use tendency.Conclusion: The findings suggest that students with lower distress tolerance and higher cognitive avoidance are more likely to exhibit a tendency toward substance use. These results underscore the importance of integrating emotional regulation and cognitive flexibility training in university-based prevention programs. Interventions targeting distress tolerance and avoidance coping could be effective in reducing the risk of substance misuse in student populations.